2015
DOI: 10.1080/02757540.2015.1022536
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of indole derivatives as antifouling agents on the growth of two marine diatom species

Abstract: Antifouling agents, used to prevent biofouling, need to be assessed for their impacts on marine organisms and environment before the application. Diatoms are one of the main components of fouling biofilms, which play important roles in the formation of biofouling. Particularly, diatoms are also the important ingredients of primary production and present interest as ecotoxicological models in marine environment. In this study, two benthic diatoms Nitzschia closterium f. minutissima and Navicula climacospheniae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…In this study, QSIs showed dose-dependent effects on the growth of diatoms and the effects were closely related to diatom species which were similar to our previous report that anti-algal activities of indole derivatives were dependent on the diatom species. [30] From the results of specific growth rates, the inhibitory activity of 4-nitropyridine-N-oxide against Cylindrotheca sp. was superior to 3,4-dibromo-2(5)H-furanone and indole.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, QSIs showed dose-dependent effects on the growth of diatoms and the effects were closely related to diatom species which were similar to our previous report that anti-algal activities of indole derivatives were dependent on the diatom species. [30] From the results of specific growth rates, the inhibitory activity of 4-nitropyridine-N-oxide against Cylindrotheca sp. was superior to 3,4-dibromo-2(5)H-furanone and indole.…”
Section: Discussionmentioning
confidence: 99%
“…Antifouling compounds also interfere with the homeostasis of cellular calcium ions (Ca 2+ ) to inhibit the attachment of fouling organisms. For example, halogenated indole derivatives (i.e., gramine, 6-chloroindole, 7-chloroindole and 6-bromoindole) can trigger the efflux of Ca 2+ from the intracellular environment and the resulting reduction in Ca 2+ abundance within cells probably contributes to the inhibition of settlement of fouling organisms (e.g., bacteria and algae) [ 10 , 11 ]. Polyphosphate, a type of orthophosphate polymer, can attach to the bacterial cell membrane and chelate the Ca 2+ there, resulting in cell death and inhibition of biofilm growth [ 12 ].…”
Section: Antifouling Compounds With Proposed Specific Targetsmentioning
confidence: 99%
“…Estas bioincrustaciones comprenden desde proteínas, polisacáridos y proteoglicanos (Maitrayee, 2012), seguido por la colonización de microorganismos como bacterias (Flemming y Wingender, 2010). Luego por diatomeas que son las principales microalgas colonizadoras de sustratos contaminados (Yang et al, 2015). Finalmente colonizan los sustratos macro organismos como invertebrados marinos, generando posteriormente una acumulación estable que provocan graves problemas (Jhaveri y Murthy, 2016).…”
Section: Introductionunclassified